2019
DOI: 10.3389/fped.2019.00414
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Gluten-Free Boom: The Dark Side of Gluten Free Diet

Abstract: In gluten dependent conditions the gluten free diet is the cornerstone of therapy, decreasing disease activity, improving health and quality of life and treating or preventing the associated complications. Gluten withdrawal implies strict and lifelong elimination not only of wheat, barley, rye, and wheat-contaminated oats, but also of numerous non-nutritional products where components of wheat are often added. Due to multiple reasons the diet is difficult to follow and the long-term adherence is decreased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 90 publications
0
51
0
5
Order By: Relevance
“…It is not clear which of these targets should be considered as the primary or secondary endpoint of GFD for CD patients towards their long-term prognosis [6]. Although safe and efficient, GFD is very restrictive, resulting as a burden on social life and quality of life (for both patients and caregivers) [7][8][9][10] and frequently with poor compliance [11][12][13]. Moreover, the clinical response to inadvertent or voluntary gluten ingestion by treated CD patients can be very heterogeneous, ranging from gastroenteritislike pictures to no symptoms [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear which of these targets should be considered as the primary or secondary endpoint of GFD for CD patients towards their long-term prognosis [6]. Although safe and efficient, GFD is very restrictive, resulting as a burden on social life and quality of life (for both patients and caregivers) [7][8][9][10] and frequently with poor compliance [11][12][13]. Moreover, the clinical response to inadvertent or voluntary gluten ingestion by treated CD patients can be very heterogeneous, ranging from gastroenteritislike pictures to no symptoms [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the nutritional profile of gluten-free food products has been increasingly questioned within the scientific community. The nutritional quality of the gluten-free food products currently available on the market is inadequate -low protein contents and high fat, sugar and salt contents-compared to equivalent gluten-containing products [52][53][54]. Data from studies on gluten-free foods have indicated that there is a need to lower fat and calories and to include more fibers, proteins, electrolytes, vitamins, and other micronutrients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many patients remain symptomatic and have ongoing low-grade enteric inflammation, despite gluten withdrawal. Admittedly, in contrast, gluten has its known side effects [46], but GFD also has a dark side [47].…”
Section: Celiac Disease In a Nutshellmentioning
confidence: 99%